Madukaku as the Basis of Being Human in (Igbo) African Worldview; A Critical Reflection - Bassey Samuel Akpan; Okpe Okpe; Timothy Adie (Budapest International Research and Critics University, 2019)
Critical understanding of Western idea of human personality reveals a lot of weaknesses. It reveals individualistic and anthropocentric tendency which is the reason for unpleasant relationship between man and fellow man and man and the environment. This kind of thinking has led Western environmental ethicist to now propound theories towards communitarian stand, for instance; deep ecology, land ethic, eco-feminism to mention a few. Enyimba, Maduka holds a radical point of view from many African communal philosophers. Maduka holds that a person is human because he/she is worth more in quality and essence than other beings and things. Such thinking has been the underlying rationale behind man’s overexploitation of nature. The thrust of the essay is to look at the basic tenets of Madukakism as the philosophy of being human in Africa. This paper agrees with the idea of Madukaku that humanity is at the centre of the universe, but differs from its individualist assumptions. In African ontology, the hierarchy of beings, God, lesser deities and ancestors are above human, If this is the case then man is not supreme and cannot be ‘the measure of all things’. Hence this paper rejects Maduka’s postulation of human being as supreme, because even within African environment there are some trees, rivers, mountains etc that are considered sacred and its therefore considered a taboo to toy with them. To this, no matter how highly placed man is, he is not allowed to touch nor exploit them, without dare consequence, which clearly shows that man is not the measure of all things but is in a complimentary state with other beings in African belief system.